Local Government and University Partnership Systems: Evidence from Cattle Beef Farmers in Barru, South Sulawesi, Indonesia - Sitti Nurani Sirajuddin; Siti Nurlaelah; Ahmad Ramadhan Siregar; Syahdar Baba; Retno Fitrianty; Abdel Razzaq Al-Tawaha (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2021)
Partnership systems still become an interesting issue to discuss. Partnerships with beef cattle farmers can be carried out by several parties, including the private sector, universities, and local governments. Therefore, this study aimed to compare the partnership systems of regional governments and Hasanuddin university from the perspective of beef cattle farmers. This study was conducted in Barru Regency, South Sulawesi Province, Indonesia, from September to December 2018. The samples comprised farmers who participated in the partnership system in Tanete Riaja Subdistrict, Barru Regency, amounting to 80 people. Farmer perceptions of the partnerships were assessed using descriptive statistics with a distribution frequency. The results showed differences in the partnership system between tertiary institutions and local governments, namely, from the system of sharing results and the different benefits obtained by farmers if partnering between universities and local governments.